Biocontrol of Bacterial Fruit Blotch by Bacillus subtilis 9407 via Surfactin-Mediated Antibacterial Activity and Colonization - Fan, Haiyan; Zhang, Zhanwei; Li, Yan; Zhang, Xun; Duan, Yongming; Wang, Qi (Frontiers in Microbiology, 2017)
In this study, Bacillus subtilis 9407 showed a strong antibacterial activity against Acidovorax citrulli in vitro and 61.7% biocontrol efficacy on melon seedlings 4 days post inoculation under greenhouse conditions. To understand the biocontrol mechanism of B. subtilis 9407, identify the primary antibacterial compound and determine its role in controlling bacterial fruit blotch, a srfAB deletion mutant (ΔsrfAB) was constructed. The ΔsrfAB which was deficient in production of surfactin, not only showed almost no ability to inhibit growth of A. citrulli but also decreased biofilm formation and reduced swarming motility. Colonization assay demonstrated that B. subtilis 9407 could conlonize on melon roots and leaves in a large population, while ΔsrfAB showed a four- to ten-fold reduction in colonization of melon roots and leaves. Furthermore, a biocontrol assay showed that ∆srfAB lost the biocontrol efficacy. In summary, our results indicated that surfactin, which consists of C13- to C16-surfactin A was the primary antibacterial compound of B. subtilis 9407, and it played a major role in biofilm formation, swarming motility, colonization and suppressing bacterial fruit blotch. We propose that the biocontrol activity of B. subtilis 9407 is the results of the coordinated action of surfactin-mediated antibacterial activity and colonization. This study reveals for the first time that the use of a B. subtilis strain as a potential biological control agent could efficiently control bacterial fruit blotch by producing surfactin. Keywords Bacillus subtilis, Acidovorax citrulli, Surfactin, Antibacterial activity, Colonization, Biological control